Pengaruh Gaya Kepemimpinan Dan Komunikasi Terhadap Kinerja Organisasi Pada Prodi Diluar Domisili (PDD) Jembrana Politeknik Negeri Bali (Rintisan Akademi Komunitas Negeri Jembrana) - Ni Komang Ardety Pramesti Indahsari; I Ketut Merta; I Made Anom Arya Pering (Universitas Mahendradatta Denpasar, 2020)
This research is based on the Effect of Leadership and Communication Style on Organizational Performance. Taking the Object of Research at the Study Program Outside Domicile (PDD) Jembrana Bali State Polytechnic (Pilot Academy of the Jembrana Country Community). The purpose of this study is to find out more about leadership style, communication and organizational performance Problem formulation: whether leadership style and communication affect organizational performance. The theoretical foundation in research uses the Management Document. Methodology: Papulation and sampling with 35 respondents, using a questionnaire list and tabulated then analyzed by multiple regression using SPSS version 24. The results of the analysis of Leadership Style yield: t count of 9.185 and significance of 0.000. t count 9.185 t table whose value is 1.69 with a significance level of 0.736 0.05. Communication produces t count of -1.922 and significance of 0.064. t count -1.922 t table whose value is 1.69 with a significance level of 0.736 0.05. Hypothesis is accepted with t count 7.263 t table 0.736, then the hypothesis which states that there is a significant positive influence between Leadership Style and Communication on Organizational Performance. The implications of the coefficient of determination (adjusted R) obtained by 75.4% indicate that the Leadership and Communication Style of organizational performance 75.4% and as much as 24.6% Leadership Style and Communication are influenced by other variables not examined in this study and can be further investigated